Arabidopsis γ-H2A.X-INTERACTING PROTEIN participates in DNA damage response and safeguards chromatin stability - Fan, Tianyi; Kang, Huijia; Wu, Di; Zhu, Xinyu; Huang, Lin; Wu, Jiabing; Zhu, Yan (Nature communications, 2022)
Upon the occurrence of DNA double strand breaks (DSB), the proximal histone variant H2A.X is phosphorylated as γ-H2A.X, a critical signal for consequent DSB signaling and repair pathways. Although γ-H2A.X-triggered DNA damage response (DDR) has been well-characterized in yeast and animals, the corresponding pathways in plant DDR are less well understood. Here, we show that an Arabidopsis protein γ-H2A.X-INTERACTING PROTEIN (XIP) can interact with γ-H2A.X. Its C-terminal dual-BRCT-like domain contributes to its specific interaction with γ-H2A.X. XIP -deficient seedlings display smaller meristems, inhibited growth, and higher sensitivity to DSB-inducing treatment. Loss-of-function in XIP causes transcriptome changes mimicking wild-type plants subject to replicative or genotoxic stresses. After genotoxic bleomycin treatment, more proteins with upregulated phosphorylation modifications, more DNA fragments and cell death were found in xip mutants. Moreover, XIP physically interacts with RAD51, the key recombinase in homologous recombination (HR), and somatic HR frequency is significantly reduced in xip mutants. Collectively, XIP participates in plant response to DSB and contributes to chromatin stability. γ-H2A.X is a critical signal for DNA double strand break responses. In this study, an Arabidopsis protein that interacts with γ-H2A.X and the recombinase RAD51 is shown to contribute to plant chromatin stability and integrity.